Imaging Diagnosis and Interventional Treatment for Hepatocellular Carcinoma Combined with Arteriovenous Fistula. (4th March 2021) - Cai, Zheng; Ran, Maohui; Song, Jiantao; Zhen, Wenrui; Li, Mingjian
Abstract : In order to explore the imaging diagnosis methods and interventional treatment effects of hepatocellular carcinoma combined with hepatic arteriovenous fistula (HAVF), a total of 120 patients, who were diagnosed as hepatic carcinoma with arteriovenous shunting and underwent medical imaging diagnosis and interventional surgery therapy at a designated hospital by this study from December 2014 to December 2018, were chosen as study subjects. Digital subtraction angiography was performed to analyze the imaging features of hepatocellular carcinoma combined with HAVF in each patient; then, according to these imaging diagnosis results, gelatin sponge or coil was used to block the fistula; mitomycin, carboplatin powder, and lipiodol mixed emulsion was combined or separately utilized for hepatic tumor embolization, in which iodized oil embolization chemotherapy was used for patients with mild paralysis; gelatin sponge granule embolization chemotherapy was used for moderate paralysis patients at their first intervention, and, after about 1 month, if the sputum disappeared, iodized oil embolization was used again; and hepatic arterial infusion chemotherapy was used only for patients with severe paralysis. The results show that the central type of HAVF is characterized by early angiography of portal vein and large branches and tumor staining after portal vein's angiography; the peripheral type of HAVF is characterized by portal vein branching in hepatic tumor and double rail sign accompanied by the arterial branch; 112 cases of patients completed embolization chemotherapy; 8 cases of patients only received chemotherapy perfusion; in 109 cases of patients sputum disappeared or shunt decreased at first treatment; and in 113 cases of patients iodine oil was well deposited or the tumor was stably reduced; most of the symptoms of refractory ascites, diarrhea, and upper gastrointestinal bleeding were controlled or improved, and there were no complications such as pulmonary embolism and hepatic failure. Therefore, HAVF increases the difficulty of interventional therapy, but, as long as the positive and appropriate treatment measures are taken, it can still achieve better curative effect without serious complications, which can effectively alleviate the clinical symptoms of patients and improve the quality of life of patients. The results of this study provide a reference for the further researches on imaging diagnosis and interventional treatment for hepatocellular carcinoma combined with arteriovenous fistula.